Odpowiedź :
Odpowiedź:
a (5/3 - 1/3 + 7/3) x 3 = 11/3 * 3 = 11
c 3 2/3 + 3 x 1 1/3 = 3 2/3 + 3 * 4/3 = 3 2/3 + 4 = 7 2/3
d 3 1/4 x 4 - 2 3/4 = 13/4 * 4 - 2 3/4 = 13 - 2 3/4 = 10 1/4
e 2 1/5 x 5 - 4 2/5 + 1 1/5 = 11/5 * 5 - 4 2/5 + 1 1/5 = 11 - 4 2/5 + 1 1/5 =
= 6 3/5 + 1 1/5 = 7 4/5
f 7 1/2 - 3 + 2 x 3/4 = 4 1/2 + 3/2 = 6
g 2 1/2 x 3 + 4 x 1 1/2 = 5/2 * 3 + 4 * 3/2 = 15/2 + 6 = 7 1/2 + 6 = 13 1/2
h 2 1/4 x 2 + 3 3/4 = 9/4 * 2 + 3 3/4 = 18/4 + 3 3/4 = 4 2/4 + 3 3/4 = 7 5/4 = 8 1/4
i 9 - 1 3/5 x 4 = 9 - 8/5 * 4 = 9 - 32/5 = 9 - 6 2/5 = 2 3/5
Odpowiedź:
w załączniku
Szczegółowe wyjaśnienie:
pozdrawiam <3